2015
DOI: 10.1530/jme-15-0140
|View full text |Cite
|
Sign up to set email alerts
|

HC toxin (a HDAC inhibitor) enhances IRS1–Akt signalling and metabolism in mouse myotubes

Abstract: Exercise enhances numerous signalling pathways and activates substrate metabolism in skeletal muscle. Small molecule compounds that activate these cellular responses have been shown to recapitulate the metabolic benefits of exercise. In this study, a histone deacetylase (HDAC) inhibitor, HC toxin, was investigated as a small molecule compound that activates exercise-induced adaptations. In C2C12 myotubes, HC toxin treatment activated two exercise-stimulated pathways: AMP-activated protein kinase (AMPK) and Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(60 reference statements)
1
13
0
1
Order By: Relevance
“…These results are consistent with previous studies on the effect by HDAC inhibition on insulin resistance in different models (5456), including in the heart of diabetic mice (15, 57, 58). Therefore, reducing insulin resistance may contribute, at certain levels, to the cardioprotection of HDAC3 inhibitor in OVE26 diabetic mouse model although the exact mechanism needs to be further explored in our future work.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies on the effect by HDAC inhibition on insulin resistance in different models (5456), including in the heart of diabetic mice (15, 57, 58). Therefore, reducing insulin resistance may contribute, at certain levels, to the cardioprotection of HDAC3 inhibitor in OVE26 diabetic mouse model although the exact mechanism needs to be further explored in our future work.…”
Section: Discussionsupporting
confidence: 93%
“…This result corresponded with previous reports that HDAC inhibitors activate the PI3K/ AKT pathway in a cell-specific manner. (23)(24)(25) In regards to HDAC inhibition, FK-A11 and FK-A3 as well as SAHA promoted acetylation of histone H3 (Fig. 3c, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Acute administration of scriptaid to mice increased the expression of exerciseresponsive metabolic genes in skeletal muscle, whereas chronic administration increased exercise performance, whole-body energy expenditure, and lipid oxidation and reduced plasma glucose and lipids (Gaur et al 2016). A number of other studies using various HDAC inhibitors have reported similar enhancements in various aspects of muscle and whole-body metabolism, including insulin sensitivity (Tan et al 2015) and enhanced oxidative capacity (Galmozzi et al 2013). The exact mechanism of action of some of these broad-spectrum HDAC inhibitors remains to be determined, but could include inhibition of HDAC3, the class I HDAC that provides deacetylase activity to the class IIa HDAC corepressor complex (Fischle et al 2002;Hudson et al 2015).…”
Section: Epigenetic Therapies To Induce Exercise Adaptationsmentioning
confidence: 85%